2010
DOI: 10.1107/s1744309110038832
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of purple nitrous oxide reductase fromPseudomonas stutzeri

Abstract: Nitrous oxide reductase (N(2)OR) from Pseudomonas stutzeri catalyzes the final step in denitrification: the two-electron reduction of nitrous oxide to molecular dinitrogen. Crystals of the enzyme were grown under strict exclusion of dioxygen by sitting-drop vapour diffusion using 2R,3R-butanediol as a cryoprotectant. N(2)OR crystallized in either space group P1 or P6(5). Interestingly, the key determinant for the resulting space group was the crystallization temperature. Crystals belonging to space group P1 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This may provide a more detailed insight of N 2 O formation regulated by Cu from an alternative pathway. The enzyme N 2 OR is considered as the only protein catalysed by Cu due to the multi‐Cu‐sulfide redox centres (Pomowski et al ., ). Surprisingly, expression of nosZ did not respond to the incensement of Cu concentration in this study, instead, the transcriptional level of nosZ decreased tremendously at 0.50 mM of Cu onward (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may provide a more detailed insight of N 2 O formation regulated by Cu from an alternative pathway. The enzyme N 2 OR is considered as the only protein catalysed by Cu due to the multi‐Cu‐sulfide redox centres (Pomowski et al ., ). Surprisingly, expression of nosZ did not respond to the incensement of Cu concentration in this study, instead, the transcriptional level of nosZ decreased tremendously at 0.50 mM of Cu onward (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While a Cu‐deficient denitrifying bacterial community can still remain viable, it is likely that they will release much higher levels of N 2 O. Several studies have documented the central role of Cu in enzyme structure and function (Matsubara et al ., ; Farrar et al ., ; Zumft, ,b; Pomowski et al ., ); however, the effects of Cu on the expression of these genes nirS , norB and nosZ to increase Cu bioavailability have yet to be described. We hypothesize that denitrifying bacteria have the ability to sense Cu availability and adjust the synthesis of N 2 OR in response to environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal microspectrometry during data collection showed that Cu A was swiftly photo-reduced at a synchrotron source, but not in data sets collected at a home source. The reduction state of Cu Z remained unchanged (Pomowski et al , 2010 ). The P. stutzeri enzyme represents the physiological state of N 2 OR and its analysis revealed several characteristic differences that are of mechanistic importance.…”
Section: Crystallographic Analysis Of N 2 Ormentioning
confidence: 98%
“…A form II enzyme was investigated from ' Achromobacter cycloclastes ' (Paraskevopoulos et al , 2006 ), an isolate from a denitrifying community (Iwasaki and Matsubara , 1972 ) that is not a taxonomically valid species by current defi nition. Recently, the purple form I enzyme from Pseudomonas stutzeri was crystallized (Pomowski et al , 2010 ), yielding a structure that represents the physiologically active form of N 2 OR (Pomowski et al , 2011 ). The structures show slight differences in the metal centers, but to date the functional implications of this variability are scarcely understood (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…-2Cu ? ] state, was reported [91]. The CuZ center in this oxidation state has not yet been extensively characterized and its structural characterization will surely give rise to new and exciting challenges.…”
Section: Future Perspectivesmentioning
confidence: 99%